Giúp với còn câu này nữa là xong r
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
đây nhé bạn! http://d3.violet.vn/uploads/previews/205/1834201/preview.swf
![](https://rs.olm.vn/images/avt/0.png?1311)
\(n_{Al}=\dfrac{5,4}{27}=0,2\left(mol\right)\)
PTHH: 2Al + 6H2SO4 --> Al2(SO4)3 + 3SO2 + 6H2O
_____0,2-------------------------------->0,3
=> VSO2 = 0,3.22,4 = 6,72 (l)
\(PTPU:2Al+6H_2SO_4\rightarrow Al_2\left(SO_4\right)_3+6H_2O+3SO_2\)
\(n_{Al}=\dfrac{5,4}{27}=0,2\left(mol\right)\\ Theo.pt:n_{SO_2}=\dfrac{3}{2}n_{Al}=0,3\left(mol\right)\\ \Rightarrow V_{SO_2}=0,3.22,4=6,72\left(l\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,=\dfrac{x^3+2x}{\left(x-1\right)\left(x^2+x+1\right)}+\dfrac{2}{x^2+x+1}-\dfrac{1}{x-1}=\dfrac{x^3+2x+2x-2-\left(x^2+x+1\right)}{\left(x-1\right)\left(x^2+x+1\right)}=\dfrac{x^3+3x-3}{\left(x-1\right)\left(x^2+x+1\right)}=\dfrac{x^3+3}{\left(x^2+x+1\right)}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\dfrac{x^3+2x+2x-2-x^2-x-1}{\left(x-1\right)\left(x^2+x+1\right)}\)
\(=\dfrac{x^3-x^2+3x-3}{\left(x-1\right)\left(x^2+x+1\right)}=\dfrac{x^2+3}{x^2+x+1}\)
b: \(=\dfrac{x^2-2x-3+x^2+2x-3+2x-2x^2}{\left(x-3\right)\left(x+3\right)}\)
\(=\dfrac{2x-6}{\left(x-3\right)\left(x+3\right)}=\dfrac{2}{x+3}\)
c: \(=\dfrac{6-7+x}{3\left(x-1\right)}=\dfrac{x-1}{3\left(x-1\right)}=\dfrac{1}{3}\)
d: \(=\dfrac{x^3+2x+2x-2-x^2-x-1}{\left(x-1\right)\left(x^2+x+1\right)}=\dfrac{x^3-x^2+3x-3}{\left(x-1\right)\left(x^2+x+1\right)}=\dfrac{x^2+3}{x^2+x+1}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
11)
\(\dfrac{2x}{x+2}\) \(\times\) \(\dfrac{x^{2^{ }}-4}{4}\) - \(\dfrac{x}{2}\)
= \(\dfrac{2x}{x+2}\) \(\times\) \(\dfrac{x^2-2^2}{4}\) - \(\dfrac{x}{2}\)
= \(\dfrac{2x}{x+2}\) \(\times\) \(\dfrac{\left(x-2\right)\left(x+2\right)}{4}\) - \(\dfrac{x}{2}\)
= \(\dfrac{x\left(x-3\right)}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
e) Ta có: \(x^3-4x-14x\left(x-2\right)=0\)
\(\Leftrightarrow x\left(x-2\right)\left(x+2\right)-14x\left(x-2\right)=0\)
\(\Leftrightarrow x\left(x-2\right)\left(x+2-14\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=2\\x=12\end{matrix}\right.\)
e)x3-4x+14x(x-2)=0
⇔ x(x2-4)+14x(x-2)=0
⇔ x(x-2)(x+2)+14x(x-2)=0
⇔ (x-2)(x2+2x+14x)=0
⇔ x(x-2)(x+16)=0
\(\Leftrightarrow\left\{{}\begin{matrix}x=0\\x-2=0\\x+16=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=0\\x=2\\x=-16\end{matrix}\right.\)
g)x2(x+1)-x(x+1)+x(x-1)=0
⇔ (x+1)(x2-x)+x(x-1)=0
⇔ x(x+1)(x-1)+x(x-1)=0
⇔ x(x-1)(x+2)=0
\(\Leftrightarrow\left\{{}\begin{matrix}x=0\\x-1=0\\x+2=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=0\\x=1\\x=-2\end{matrix}\right.\)